Fabrication and Characterization of Translucent Wood Composite Using Egyptian Hardwoods: Casuarina & Eucalyptus - Elia, Sherif (AUC Knowledge Fountain, 2021)
Due to climate change and global warming, there is an increasing need for sustainable solutions in all industries. As one of the most important and growing industries worldwide, the construction industry has a huge responsibility towards the environment. It is responsible for the consumption of vast amounts of resources and consequently generating massive quantities of waste. Also, as the building sector is responsible for consuming large portions of the world energy and electricity, such buildings' efficiency and sustainability must be considered. While the world is working on balancing between consuming less and recycling more while maintaining the construction materials' effectiveness and efficiency, there is an immense need to develop more sustainable building materials that can increase buildings' efficiency while decreasing the effects on the environment. Thus, introducing transparent wood composite, which is basically fabricated using delignified wood pieces or fibers with a polymer, can be used in many different applications due to its advantages over other materials [1]. Due to its better thermal insulation compared to regular glass, it can be used in buildings' cladding to reduce its carbon footprint through proper insulation and adequate natural lighting. Accordingly, decreasing the energy and electricity required to ventilate and temperature control as well as the need for natural lighting. Consequently, saving tons of GHG emissions, which significantly contribute to global warming and air pollution and help preserve our environment. Also, it has high potential in solar energy due to its "high optical haze". Finally, on top of the benefits mentioned above, transparent wood is considered a sustainable material, to replace plastics and other materials, due to its better biodegradability [2]. The aim of this study is to fabricate transparent wood using Egyptian hardwoods (Casuarina & Eucalyptus) and optimize the fabrication process. First, a pilot study was conducted to design the experimental setup; then, three chemical treatment recipes were used to determine the most effective method. Moreover, the lignin modification method was selected for an in-depth study for lignin quantification using Klason lignin for both wood species. Since Casuarina had less lignin content (to begin with (29% compared to 35% for Eucalyptus), it required little to no further treatment after the end of the first treatment process. Consequently, Casuarina wood was selected for the fabrication of transparent wood iii using the lignin modification method showing good optical properties with 72% transmittance and 95% haziness. Also, TWS was fabricated from Casuarina sawdust using the lignin modification method and showed better overall high optical properties with transmittance around 80% and haziness of 85%. Therefore, a scalable treatment process for sawdust was tried using commercial bleach to introduce a more feasible method. Finally, the optical properties for the TW and TWS were compared to three types of glass (regular, sanded, and rain glass) as an alternative material in which the TWS showed comparable light transmittance compared to regular and rain glass with 85% and 82% respectively. At the same time, TW had similar results to the sanded glass, which had around 72% light transmittance. On the other hand, TW had the highest optical haze with 95%, followed by TWS and sanded glass with 77% showing a better overall behavior for TW and TWS over the glass.